2020
DOI: 10.3389/fncel.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β and Tau Protein in Alzheimer’s Disease and Epilepsy

Abstract: Alzheimer's disease (AD) is the most common form of dementia present in older adults; its etiology involves genetic and environmental factors. In recent years, epidemiological studies have shown a correlation between AD and chronic epilepsy since a considerable number of patients with AD may present seizures later on. Although the pathophysiology of seizures in AD is not completely understood, it could represent the result of several molecular mechanisms linked to amyloid beta-peptide (Aβ) accumulation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 85 publications
(105 reference statements)
0
78
0
2
Order By: Relevance
“…Moreover, the α7 nAChRs could support the synaptic plasticity and cognition by activating the protein kinases phosphoinositide-3 kinase (PI3K), Akt, extracellular signal-regulated kinase 1/2 (ERK1/2) and the transcription factor CREB [ 23 ]. GSK3β is a proline-directed kinase and is considered to be the main kinase that phosphorylates tau protein, the major component of NFTs observed in AD [ 71 ]. It has been demonstrated that Akt pathway stimulation by COT inhibits GSK3β by phosphorylation in the brains of AD mice [ 30 , 72 ] and restrained mice [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the α7 nAChRs could support the synaptic plasticity and cognition by activating the protein kinases phosphoinositide-3 kinase (PI3K), Akt, extracellular signal-regulated kinase 1/2 (ERK1/2) and the transcription factor CREB [ 23 ]. GSK3β is a proline-directed kinase and is considered to be the main kinase that phosphorylates tau protein, the major component of NFTs observed in AD [ 71 ]. It has been demonstrated that Akt pathway stimulation by COT inhibits GSK3β by phosphorylation in the brains of AD mice [ 30 , 72 ] and restrained mice [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…GSK3β has been centrally implicated in AD pathogenesis (Forlenza et al, 2014;Kerr et al, 2018;Hampel et al, 2019), affecting both the overproduction of the amyloid-beta peptide (Aβ) and hyperphosphorylation of microtubule-associated protein Tau, mechanisms that respectively lead to the formation of senile plaques and neurofibrillary tangles-pathological hallmarks of AD (Tan et al, 2010;Forlenza et al, 2014;Kerr et al, 2018;Hampel et al, 2019;Li et al, 2020). Lithium is a potent inhibitor of GSK3β activity (Engel et al, 2006;Tan et al, 2010;Forlenza et al, 2014;Kerr et al, 2018;Hampel et al, 2019;Li et al, 2020) and, in animal models of AD, chronic lithium treatment was associated with reduced hyperphosphorylation of Tau and Aβ accumulation (Su et al, 2004;Noble et al, 2005;Engel et al, 2006;Forlenza et al, 2014). Clinical extrapolations of these effects are scarce, but the available evidence from a small number of clinical trials seem to be in line with experimental findings (Forlenza et al, 2011b,c;Ladeira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the result of (Salama et al, 2018) proved that the Serum's Tau was higher in patient with AD than the Parkinson disease. Increased expression of tau protein may lead to the risk of a pathological accumulation and deposition of the protein in its ibrillary form, as con irmed by (Götz et al, 2007)in their study on animal models .Another study accomplished by (Toral-Rios et al, 2020)demonstrated that the over expressed of tau protein lead to the deposition and accumulation of this protein as neuro ibrillary tangles (NFTs) in the brain tissue of temporal lobe epilepsy TLE patients with an increase of glycogen synthase kinase-3 beta, GSK3b hyperactivity may cause posttranslational modi ications of some microtubule-associated proteins (MAPs), specially tau.…”
Section: Tau Protein Concentrationmentioning
confidence: 96%